Síntese e caracterização de catalisadores de óxido de ferro suportado em titanatos lamelares - BRASIL, Valéria Bacelar (2008)
Sodium trititanate and silica - trititanate supported iron oxide catalysts were prepared by coprecipitation of iron ions and by the deposition of iron oxide nanoparticles previously prepared. The catalysts and the supports were characterized regarding their composition, structure, thermal behavior and textural properties. The amount of iron in catalysts ranged from 0.98% to 5.9%, and the lowest percentages were observed for catalysts prepared by deposition of nanoparticles. The catalysts and supports are macroporous with limited mesoporosity. The catalysts and supports were evaluated in the reaction of dehydrogenation of ethylbenzene for the production of styrene. During tests, the structure of the solids did not chang. Both the supports and the catalysts were active in the dehydrogenation of ethylbenzene in the absence of steam, allowing the economy of energy. The results of verification of the ionic exchange process/ adsorption of Cu+2, showed that the solids containing iron oxide in the composition presented results higher than the solids without iron oxide. The exception was observed for the solids that have acid surface.